Psychometric Properties of the Moore Index of Nutrition Self-Care in Arabic: A Study among Saudi Adolescents at King Saud University, Riyadh, Saudi Arabia - Adel Bashatah; Khalid A. Alahmary (Nursing Research and Practice)
Background and Objective. The Moore Index of Nutrition Self-Care (MIN-SC) questionnaire has been used widely in both English and Spanish languages. The purpose of this study is to convert MIN-SC into the Arabic language and to test the translated tool for validity and reliability among adolescents in Saudi Arabia. Method. The psychometric characteristics of MIN-SC were assessed using college freshman students at King Saud University in Riyadh, Saudi Arabia. The validity and reliability were examined using Cronbach’s alpha coefficient. The construct validity was examined through principal component analysis. Results. The MIN-SC instrument was shown to be internally consistent with reliable scoring (Cronbach’s alpha = 0.910). Exploratory factor analysis resulted in 42 items loading on three main components: estimative, production, and transitional, with a factor loading of eigenvalues >2. The final model explained 38% of the variance. Conclusion. The Arabic version of MIN-SC was shown to be a valid and reliable tool for assessing attitude toward nutrition among adolescent students.